2016
DOI: 10.1016/j.ejrad.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Positive predictive values by mammographic density and screening mode in the Norwegian Breast Cancer Screening Program

Abstract: PPVs decreased by increasing MD. Fewer women needed to be recalled or undergo an invasive procedure to detect one breast cancer among those with fatty versus dense breasts in the screening program in Norway, 1996-2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 152 publications
(229 reference statements)
0
6
0
Order By: Relevance
“…Results were essentially unchanged when we excluded the family history screenees, so they apply specifically to women recalled for assessment due to a suspicious screening mammogram. One would expect a smaller effect of density on risk in assessment cases as these would be likely to have higher levels of density on average than the general population, as women with denser breasts have mammography results harder to read and tend to be recalled more often [45] . Our results indicate that the effect in this group, while smaller than observed in the general screened population [2] , is by no means negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Results were essentially unchanged when we excluded the family history screenees, so they apply specifically to women recalled for assessment due to a suspicious screening mammogram. One would expect a smaller effect of density on risk in assessment cases as these would be likely to have higher levels of density on average than the general population, as women with denser breasts have mammography results harder to read and tend to be recalled more often [45] . Our results indicate that the effect in this group, while smaller than observed in the general screened population [2] , is by no means negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated MBD has been consistently associated with an increased risk of breast cancer (2)(3)(4). However, high MBD can "mask" an emerging tumor on standard mammography and therefore requires additional supplemental diagnostic tools (5,6). Ultrasound (US) screening is now receiving increased attention as a proven supplemental screening tool to differentiate between benign and malignant breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The positive predictive values for BI-RADS 4a were defined as 2-10%, BI-RADS 4b as 10-50%, and BI-RADS 4c as 50-95% (7). BI-RADS 4 masses with dense breasts have a moderately increased risk of breast cancer, and dense breasts substantially reduced the sensitivity of mammography to detect malignancy (4,6). As we known, it is particularly difficult for radiologists to consistently distinguish the two most common and most variably assigned BI-RADS categories.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, an automated volumetric breast density assessment software (Volpara TM ) (27) was temporarily installed at two screening units for quality assurance and enhancement of the screening program. The three-point scale has been used for annual national reports on early performance measures in the screening program (28) and for the research on the impact of mammographic density on screening performance (29,30). Previous studies using the three-point scale have shown significantly higher positive predictive values and more favorable prognostic tumor characteristics for women with low versus high mammographic density (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…The three-point scale has been used for annual national reports on early performance measures in the screening program (28) and for the research on the impact of mammographic density on screening performance (29,30). Previous studies using the three-point scale have shown significantly higher positive predictive values and more favorable prognostic tumor characteristics for women with low versus high mammographic density (29,30). However, the three-point scale has never been validated with respect to automated density assessment.…”
Section: Introductionmentioning
confidence: 99%